Integrity in Public Service in the City of Tomohon - Djonny Pabisa (Journal Research of Social Science, Economics, and Management, 2022)
The focus of this research is on the aspects of public service delivery, the application of integrity values ??by state civil servants and the community, as well as the efforts made to optimize the application of integrity values ??in public services at the Tomohon City public service mall. Using a qualitative research approach with descriptive methods. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Data were collected through observation, interviews, and documentation. The research findings show: 1) The implementation of public services by the Tomohon City Public Service Mall is based on the Tomohon Mayor Regulation Number 11 of 2018. In the midst of the covid-19 pandemic, it is carried out in 4 ways, namely physical distancing, online services, normal direct services (public come to take care of themselves), and walk-in or mobile service, 2) The application of the value of integrity by state civil servants at the public service mall of Tomohon City and the service user community is still not fully in line with the desired expectations. Although several applications of integrity values ??already exist which are categorized as good and very good, some are categorized as not good, and 3) The Tomohon City Government through the public service mall has made various efforts to optimize the implementation of public services to the community, including optimizing the application of integrity values ??in any ongoing public service process. These efforts are in the form of direct coaching, technical guidance, mentoring, building open communication between all components, providing complaint box facilities both physically and electronically, providing motivation and education, monitoring and evaluation, awarding, online use, and online-based services.